Impact of media trust and personal epidemic experience on epidemic prevention behaviors in the context of COVID-19: A cross-sectional study based on protection motivation theory - Zhang, Dan; Su, Fan; Meng, Xiaoxia; Zhang, Zhixin (Frontiers in Public Health, 2023)
Objective: This study aimed to elucidate the impact of media trust on epidemic prevention motivation and behaviors based on the Protection Motivation Theory (PMT) and to evaluate the moderation effect of personal epidemic experience, which focused on the differences in two groups with or without epidemic experience. Methods: The exogenous constructs and PMT model and scale were constructed through literature analysis, and a web-based questionnaire survey was conducted among 428 individuals aged above 18 years in China. Statistical analysis and hypothesis testing were performed in SPSS 26 and SmartPLS 3. Results: Traditional media trust accounted for the largest weight in media trust (w=0.492, P-value<0.001), followed by social media (w=0.463, P-value<0.001), and interpersonal communication (w=0.290, P-value<0.001). Media trust was positively and significantly related to both threat appraisal (β=0.210, P-value<0.001) and coping appraisal (β=0.260, P-value<0.001). Threat appraisal (β=0.105, P-value<0.05) and coping appraisal (β=0.545, P-value<0.001) were positively and significantly related to epidemic prevention motivation, which positively and significantly related to epidemic prevention behaviors (β=0.492, P-value<0.001). The R2 values of epidemic prevention motivation and behavior are 0.350 and 0.240, respectively, indicating an acceptable explanation. Multiple-group analysis revealed five significant differences in paths between the two groups, indicating personal epidemic experience acting as a slight moderator on these paths. Conclusions: Traditional media trust and social media trust were the important elements in COVID-19 prevention and control, and public health departments and governments should ensure the accuracy and reliability of information from traditional and social media. Simultaneously, the media should balance threat information and efficacy information in order to generate the public’s prevention motivation and behaviors.